Historiography of educational process in madrasahs of Bukhara Emirate (XVIII-XIX centuries) (Eurasian Journal of Humanities and Social Sciences, 2023)
In the 18th-19th centuries, education in madrasas of the Bukhara emirate was carried out at three levels: primary (adno), middle (avrot), and higher (allo). Classes in madrasahs were mainly held in the form of active discussion. For example, teacher Ikromcha started the lesson by putting a question for the madrasa students to discuss. He explained the essence of the matter. By focusing the students' thoughts on one goal, after they had finished arguing, he turned his attention to himself. Then he explained the content of the studied text in Tajik language with convincing examples and concrete arguments and expressed his attitude to the author's opinion. This article provides important information on the historiography of the educational process in the higher madrasas of the Bukhara Emirate. The students learned the book "Avvali Ilm" by heart in a few days. "Avvali Ilm" is a Persian language study guide that teaches the fundamentals of Islam in the form of questions and answers. The answer to the question is to know Allah, to know the Prophet, to understand Satan